PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN BAGI IBU RUMAH TANGGA DALAM MENGELOLA KEUANGAN DI KELURAHAN SUKAJADI TANGERANG - Desta, Christy (Jurnal Abdi Citra, 2024)
In Sukajadi Subdistrict, Tangerang, there are still people who lack knowledge regarding household financial management, especially in recording financial income and expenditure, where many residents experience household problemsand conflicts due to economic factors or poor family finances. Financial recording is not yet running, so it cannot show the level of success in the household, financial reports can also be used for decision making in the household and poor financial reports can create vulnerability to errors due to poor economic factors. The expected results and outcomes of community serviceare that women in Sukajadi subdistrict can implement household financial planning, make a budget using percentages according to needs to minimize unnecessary expenses, and separate records of financial income and expenditure correctly, so that they can invest. for the future, so that household finances will be controlled and a prosperous family can be achieved, as well as increasingknowledge about financial management so that households avoid economic problems.